2018
DOI: 10.3892/mmr.2018.8909
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the protein profile in saliva during physiological term and preterm delivery

Abstract: From a clinical point of view, easily obtainable and useful markers of a particular pathological status are required for appropriate diagnosis and treatment. Analysis of the proteomic profile of saliva may allow for the selection of potential marker of preterm delivery in humans. Saliva samples were collected from 12 patients diagnosed with threatened preterm delivery and 10 controls with uncomplicated pregnancies at the same gestational age. Samples were analysed using 2D electrophoresis. Based on statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Our 34 study participants who fulfilled the inclusion criteria for this study represent the semi-urban population of a northern state in India. The median age of the participants was 23 (interquartile range (IQR) 20, 23) years and 24 (IQR,22,25) years respectively for the discovery and the validation cohorts (Table 1). All subjects delivered at term and had a baby with appropriate body weight for age ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our 34 study participants who fulfilled the inclusion criteria for this study represent the semi-urban population of a northern state in India. The median age of the participants was 23 (interquartile range (IQR) 20, 23) years and 24 (IQR,22,25) years respectively for the discovery and the validation cohorts (Table 1). All subjects delivered at term and had a baby with appropriate body weight for age ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the level of anti-inflammatory protein Annexin-1 in the saliva is shown to be elevated in pregnant women with gingivitis 21 . Recent 2D-gel based-proteomics analysis of saliva from pregnant women who deliver premature babies has identified a Metallothionein 2 (MT2A) protein as a potential marker for preterm birth prediction 22 .…”
mentioning
confidence: 99%
“…Human studies, however, provided many examples of the use of saliva parameters as diagnostic tools in the estimation of delivery time [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that MT2A present in saliva could be a potential biomarker for the risk of premature delivery. Notwithstanding this, additional research is necessary to confirm these results [46].…”
Section: Gdm and Oxidative Stressmentioning
confidence: 91%
“…Salivary MDA and the inactivation of ALDH could be biomarkers for OS in the oral cavity. Screening the saliva of pregnant women for OS biomarkers could prove beneficial for oral health problems, gestational diabetes, or even premature delivery [46]. One study found that MT2A present in saliva could be a potential biomarker for the risk of premature delivery.…”
Section: Gdm and Oxidative Stressmentioning
confidence: 99%